Bones in human CYP26B1 deficiency and rats with hypervitaminosis A phenocopy Vegfa overexpression - Lind, Thomas (Bone Rep, 2018)
Angulated femurs are present prenatally both in CYP26B1 deficient humans with a reduced capacity to degrade retinoic acid (RA, the active metabolite of vitamin A), and mice overexpressing vascular endothelial growth factor a (Vegfa). Since excessive ingestion of vitamin A is known to induce spontaneous fractures and as the Vegfa-induced femur angulation in mice appears to be caused by intrauterine fractures, we analyzed bones from a CYP26B1 deficient human and rats with hypervitaminosis A to further explore Vegfa as a mechanistic link for the effect of vitamin A on bone. We show that bone from a human with CYP26B1 mutations displayed periosteal osteoclasts in piles within deep resorption pits, a pathognomonic sign of hypervitaminosis A. Analysis of the human angulated fetal femur revealed excessive bone formation in the marrow cavity and abundant blood vessels. Normal human endothelial cells showed disturbed cell-cell junctions and increased CYP26B1 and VEGFA expression upon RA exposure. Studies in rats showed increased plasma and tissue Vegfa concentrations and signs of bone marrow microhemorrhage on the first day of excess dietary vitamin A intake. Subsequently hypervitaminosis A rats displayed excess bone formation, fibrosis and an increased number of megakaryocytes in the bone marrow, which are known characteristics of Vegfa overexpression. This study supports the notion that the skeletal phenotype in CYP26B1 deficient human bone is caused by excess RA. Our findings suggest that an initial part of the vitamin A mechanism causing bone alterations is mediated by excess Vegfa and disturbed bone marrow microvessel integrity.